Dispatching Policies in Distributed Service Networks: Analyzing the Impact of Different Dispatching Policies on Performance in Distributed Service Networks (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A service network is a resource and process structure, which works with the consumer and delivers performance. Since most of the business networks are labor intensive, company workers are the primary re-sources. Thanks to several criteria and combinations, the architecture of such operating structures is non-trivial, but essential for business decisions in the workplace. The most critical concept factor for a management program is whether and where resources are delegated to staff who submit policies. This paper offers a basis for the evaluation of dispatch practices in operation networks. A discrete operating network modeling model in the data center management domain is provided. They test four dispatch regulations on five real-life systems. We note that the simulation-based method integrates nuanced aspects of service structures and allows for a comparative analysis of dispatch policies which results in more detailed decisions on jobs.